A Educação de Jovens e Adultos na Escola Municipal Professor Ladário Teixeira: concepção histórica, gênese, vivências e experiências (2005-2015) - Bernardes, Fernanda Afonso (2022)
This study was carried out within the scope of the Graduate Program in Education at the Federal University of Uberlândia, linked to the line of History and Historiography of Education. The doctoral thesis presents a historical – education research on the historical conception, genesis, experience and experience of Education of young people and adults at Professor Ladário Teixeira High School, during the period from 2005 to 2015, in the city of Uberlândia, M.G. The time frame of the research starts from 2005 to 2015, a fact that is justified by the Opinion nº5/ 2005 that establishes the Curricular Guidelines for the Pedagogy course, and the Opinion 2/ 2015 that establishes the National Curriculum Guidelines for Education Initial and Continuing Training for Professionals in Basic Education, emphasizing the importance of Initial Training for pedagogical practice. The research aimed to understand the experiences and experiences of pedagogical practices developed in the school during the proposed period. Fulfilling this objective meant building a historical understanding of the political, social and economic intention underlying the education of young people and adults in our country, in our state and in our municipality; present a systematized understanding of EJA’s public policies; to collect data from existing research related to the theme of Youth and Adult Education in some of the main universities in our country, analysis of documents related to EJA in Professor Ladário Teixeira High School, in order to unveil the experiences and experiences in the institution that contributed to the formation of the subjects involved in the teaching and learning process of this teaching modality. The research used documental analysis as a method to analyze articulations, relationships, tensions and contradictions in the movement underlying youth and adult education. The historical sources included legislation, analysis of class diaries, school regiment, political and pedagogical project, photographic archive of developed projects. The theoretical basis is based on reference authors in the history of youth and adult education, produced by researchers such as Arroyo (2001), Buffa (1990), Haddad and Di Pierro (2000), Freire (1989), Gadotti and Romão (2001), Saviani (2008), among others. The research outlined national, state and regional elements related to the education of young people and adults, in addition to the conception of education and literacy developed throughout the historical course of EJA in our country. The research pointed out the importance of the pedagogical practice developed at Professor Ladário Teixeira High School in order to form citizens who are aware of their role in interfering in the society in which we live.